EFEKTIVITAS PROGRAM FARDHU ‘AIN DALAM MEMBENTUK AKHLAK MULIA SISWA DI TADIKA DIDIK BISTARI GEMILANG GERIK MALAYSIA - Yuli Syahpitri Manurung; zailani (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2026)
This study aims to determine the extent of effectiveness of the Fardhu 'Ain Program in developing noble character among students at Tadika Didik Bistari Gemilang, Gerik, Perak, Malaysia. As a fundamental pillar of Islamic education, the Fardhu 'Ain Program focuses on fundamental individual obligations, including basic beliefs and practical worship. This study employed a descriptive qualitative methodology, employing data collection techniques such as field observations, in-depth interviews with teachers and parents, and documentation analysis. The findings indicate that the program serves as a transformative instrument, successfully bridging the gap between theoretical religious knowledge and daily practical application. By implementing visual demonstration and storytelling methods, the School has fostered spiritual independence in children through the use of visual demonstration and storytelling techniques. This is demonstrated by the students' regular habit of reciting prayers spontaneously every day. The program also significantly improved students' interpersonal intelligence, demonstrated by polite communication and proactive social empathy. Important findings highlight students' spiritual initiatives, such as spontaneous recitation of Surah Al-Fatihah in a grieving environment, which reflects deep moral courage and internalized faith. Ultimately, this study concludes that the Fardhu 'Ain Program is highly effective in developing a holistic personality that harmonizes the relationship between the servant and the Creator with social responsibility towards fellow human beings, producing a generation that is intellectually competent and morally exemplary.